Designs of Splints for Preventing Skin Graft Contraction and Study of their effectiveness - C. P. Sawhney (Indian Journal of Plastic Surgery)
The rationale and design of splints to be worn after release of contractures has been presented. Whereas compression splints need to be worn for 6 months, the traction splints have to be muaintained for longer peri ds. The compression splints are more crective than traction splints in preventing contraction of skin grafts.